Possible mechanisms of SARS-CoV-2-associated myocardial fibrosis: reflections in the post-pandemic era - Wang, Zhan; Li, Luwei; Yang, Shuai; Li, Zhengrui; Zhang, Pengpeng; Shi, Run; Zhou, Xing; Tang, Xiaojuan; Li, Qi (Frontiers in Microbiology, 2024)
Since December 2019, coronavirus disease 2019 (COVID-19) has been spreading worldwide with devastating immediate or long-term effects on people's health. Although the lungs are the primary organ affected by COVID-19, individuals infected with SARS-CoV-2 also develop systemic lesions involving multiple organs throughout the body, such as the cardiovascular system. Emerging evidence reveals that COVID-19 could generate myocardial fibrosis, termed "COVID-19-associated myocardial fibrosis". It can result from the activation of fibroblasts via the renin-angiotensin-aldosterone system (RAAS), transforming growth factor-β1 (TGF-β1), microRNAs, and other pathways, and can also occur in other cellular interactions with SARS-CoV-2, such as immunocytes, endothelial cells. Nonetheless, to gain a more profound insight into the natural progression of COVID-19-related myocardial fibrosis, additional investigations are necessary. This review delves into the underlying mechanisms contributing to COVID-19-associated myocardial fibrosis while also examining the antifibrotic potential of current COVID-19 treatments, thereby offering guidance for future clinical trials of these medications. Ultimately, we propose future research directions for COVID-19-associated myocardial fibrosis in the post-COVID-19 era, such as artificial intelligence (AI) telemedicine. We also recommend that relevant tests be added to the follow-up of COVID-19 patients to detect myocardial fibrosis promptly. COVID-19 can cause systemic lesions involving multiple organs throughout the body. Myocardial fibrosis refers to excessive collagen deposition in the heart, a marked increase in the collagen volume fraction, and the imbalanced proportion and crosslinking of various collagens. Myocardial fibrosis is a troublesome problem in the cardiovascular system and can entail severe manifestations such as arrhythmias and ventricular diastolic dysfunction. Unfortunately, there is currently no effective therapy for preventing myocardial fibrosis. Emerging evidence reveals that COVID-19 could generate myocardial fibrosis (termed "COVID-19-associated myocardial fibrosis"). Cardiac injury and cardiomyopathy have been focused on by scientists as common complications of COVID-19 infection. Myocardial fibrosis is an important cause of COVID-19-induced cardiomyopathy. Herein, we elucidate the potential mechanisms of COVID-19-associated myocardial fibrosis and explore the antifibrotic value of existing COVID-19 therapeutic agents. Ultimately, we propose future research directions for COVID-19-associated myocardial fibrosis in the post-COVID-19 era.